2020
DOI: 10.3390/app10061980
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Temperature Distribution in CRTS-II Ballastless Tracks on a High-Speed Railway Bridge

Abstract: To study the temperature distribution in the China Railway Track System Type II ballastless slab track on a high-speed railway (HSR) bridge, a 1:4 scaled specimen of a simply-supported concrete box girder bridge with a ballastless track was constructed in laboratory. Through a rapid, extreme high temperature test in winter and a conventional high temperature test in summer, the temperature distribution laws in the track on the HSR bridge were studied, and the vertical and transverse temperature distribution tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…However, prolonged operation could cause various defects in track slabs, such as warping deformation of track slab [4,5], wide and narrow joint damages [6,7], interlayer debonding [3,8,9], and arching deformation of track slab [10][11][12]. Under temperature load [13,14] and high-frequency train load [14], these damages may cause track slab deformation and abnormal vibrations in wheel-rail system. Considering the complex external factors, the performance of track slab is spatially and temporally variable, so the occurrence of track slab damage is sudden and unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…However, prolonged operation could cause various defects in track slabs, such as warping deformation of track slab [4,5], wide and narrow joint damages [6,7], interlayer debonding [3,8,9], and arching deformation of track slab [10][11][12]. Under temperature load [13,14] and high-frequency train load [14], these damages may cause track slab deformation and abnormal vibrations in wheel-rail system. Considering the complex external factors, the performance of track slab is spatially and temporally variable, so the occurrence of track slab damage is sudden and unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…The overall temperature action causes the expansion, while temperature gradient causes flexural deformations in the structure [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The changes in ambient temperature cause temperature changes within the track structure, and a complex thermal field is generated inside the structural system [ 21 , 22 , 23 , 24 , 25 ]. Regarding the thermal field in the track slab, Gao Liang et al [ 19 ] studied the characteristics of track slab surface temperature following the change of ambient temperature through long-term temperature monitoring and formulated a relationship between track slab surface temperature and ambient temperature using a quartic polynomial and exponential distribution model.…”
Section: Introductionmentioning
confidence: 99%
“…Ou Zumin et al [ 21 ] formulated the extreme value probability distribution model of track slab temperature based on probability demand and theoretical derivation; they concluded that a reasonable value of thermal load could be determined using the model. Zhao Lei et al [ 22 ] analyzed the distribution of two-dimensional temperature fields in CRTS Ⅱ ballastless tracks and put forward the three-dimensional distribution pattern of horizontal and vertical temperature in track systems by carrying out the temperature test under typical high-temperature weather in a laboratory. Based on the experimental study, Zhang Guangchao et al [ 23 ] observed that the stiffness of the track structure gradually degenerated under cyclic thermal load, which induced the separation between the track slab and the CA mortar layer.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming a sudden rise or drop of ambient temperature happens, the differences in temperature boundaries will cause inhomogeneous temperature change and induce large nonlinear temperature gradients. The nonlinear temperature gradients along the directions of height, the width of the beam, and thickness of plate unquestionably cause significant deformation and stress of temperature under constraints [17][18][19], which threaten the safety and serviceability [11,20] of aqueducts. Thus, the study of thermal stress of an aqueduct is a significant aspect of the design process, and temperature distribution is the prerequisite for stress analysis.…”
Section: Introductionmentioning
confidence: 99%